Sports technologies: Implementation in the practice of higher education institutions - Sterlikova, Veronika Y.; Eremina, Ekaterina A. (Физическое воспитание и студенческий спорт, 2025)
The article examines modern trends in the field of sports technologies, their implementation in practice of innovative sports, such as phygital sports, computer sports, drone racing, laser combat and sports programming, their regulatory framework. The key barriers limiting development of sports technologies are considered, and ways to overcome them are proposed. Classification of sports technologies is made based on their functionality and scope of application. Results of the study can be useful for designing practical recommendations for improving the processes of development and application of sports technologies in the higher education system.